Development of Science Learning Interactive Media Based Lectora Inspire to Improve Students' Critical Thinking Skills - Wardani, Devanti Tris; Wahyuni, Sri; Wahyuni, Diah; Juwandoko, Juwandoko (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Interactive learning media is one of the digital learning media that is used as a means of delivering two-way or more communication information in learning. The purpose of this study was to determine thevalidity, practicality, and effectiveness of interactive media based lectora inspire on students' criticalthinking skills. The type of research used is research and development (R&D). The research subjects inthis study were 26 students class VII of SMPN 5 Jember in the academic year 2022/2023. The results ofthe development research show that: (1) the validation test shows an assessment of interactive mediabased on lectora inspire obtained from experts 82.95% is declared valid, (2) the practicality test obtains apercentage value of 92.19% which is stated to be very practical to use in learning , (3) the N-gain testobtained a score of 0.61 which was declared effective for improving students' critical thinking skills inlearning science